Enhancing Financial Governance: Compliance with Government Accounting Standards in Educational Institutions - Khazbiika Teresia; Sezen Tirsa (Indonesia Auditing Research Journal, 2023)
This research investigates the implementation of government accounting standards in educational institutions and its implications for financial governance within the education sector. Drawing upon a mixed-method approach, the study examines compliance levels, challenges, and influential factors shaping the adoption and adherence to accounting regulations among educational institutions. Findings reveal varying levels of compliance, with resource constraints, organizational complexity, limited accounting expertise, regulatory complexities, and resistance to change identified as key implementation challenges. Despite these obstacles, proactive strategies and collaborative efforts among stakeholders are essential for enhancing compliance, transparency, and accountability in financial management practices. The research underscores the importance of prioritizing compliance with government accounting standards to strengthen financial governance, build public trust, and better serve the needs of students and communities. By addressing implementation challenges and fostering a culture of accountability, educational institutions can fulfill their mission of providing quality education and contributing to societal progress.